Conceptual confusion and potential advances in athlete burnout research - Gustafsson, H.; Lundkvist, E.; Podlog, L.; Lundqvist, C. (Perceptual and Motor Skills, 2016)
More than 30 years of research on athlete burnout has yielded important insights and questions regarding the onset, nature, and consequences of this detrimental syndrome. Not surprisingly, burnout is considered an important matter, both from a research and practical standpoint. We comment on the work of Ryu, Ali, Kim, Choi, and Radlo, who examined the impact of burnout on cognitive performance among athletes. ABSTRACT FROM AUTHOR